2005
DOI: 10.1007/s11137-005-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Iodine, Cesium, and Strontium Radionuclides on Alkaline-Earth Hydroxyphosphates from Aqueous Solutions

Abstract: Sorption of 131 I ! , 131 IO 3 ! , 137 Cs + , 85 Sr 2+ , and F ! ions on synthesized alkaline-earth (AE) (calcium, strontium, and barium) hydroxyphosphates was studied. These hydroxyphosphates were prepared by the reactions MCl 2 + Na 3 PO 4 + NaOH = M 5 (PO 4 ) 3 OH; MCl 2 + NH 4 OH + (NH 4 ) 2 HPO 4 = M 5 (PO 4 ) 3 OH; and MCl 2 + NaOH + (NH 4 ) 2 HPO 4 = M 5 (PO 4 ) 3 OH (M = Ca, Sr, Ba). All the tested AE hydroxyphosphates do not sorb ionic species of radioactive iodine from aqueous solutions. The highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/30/15 1:15 PM was found that the uptake percentages attained after equilibrium are 82% and 61% for adsorption onto iron ferrite and natural magnetite, respectively. Kulyukhin et al [11] investigated the sorption of 131 I, 137 Cs, 85 Sr and F − ions on synthesized alkaline earth (AE) (calcium, strontium and barium) hydroxyphosphate. The results obtained showed that the degree of 137 Cs and 85 Sr sorption recovery from aqueous solutions upon their 120 min contact with AE hydroxyphosphate is ∼ 5-25% and ∼ 15-80%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/30/15 1:15 PM was found that the uptake percentages attained after equilibrium are 82% and 61% for adsorption onto iron ferrite and natural magnetite, respectively. Kulyukhin et al [11] investigated the sorption of 131 I, 137 Cs, 85 Sr and F − ions on synthesized alkaline earth (AE) (calcium, strontium and barium) hydroxyphosphate. The results obtained showed that the degree of 137 Cs and 85 Sr sorption recovery from aqueous solutions upon their 120 min contact with AE hydroxyphosphate is ∼ 5-25% and ∼ 15-80%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A study has been made of the adsorption of americium onto a-alumina 220 and of [ 99 Mo]molybate anions onto hydrated aluminas. 221 Similarly it has been found that uranyl cations are adsorbed by hydroxyapatite, 222 that iodine, caesium and strontium radionudlides are adsorbed onto hydroxyphosphates 223 and that rare earth, neptunium and plutonium ions can be adsorped 224 onto calcite. Stronium-90 cations are adsorbed 225 onto the structurally similar magnesite and also onto kaolinite.…”
Section: Adsorptionmentioning
confidence: 98%
“…Sylvester's measurements on Nanonatitanate yielded a K d of 3.2 × 10 4 mL/g, and Na-titanate yielded a K d of 5.8 × 10 4 mL/g (Marinin and Brown 2000). Many calcium-based minerals were tested, but most produced very low K d values (Vojtěch et al 1974;Song et al 2013;Ivanets et al 2014;Kulyukhin et al 2005). Only Ca-alginate beads in a solution without competing cations produced a maximum K d of 1.6 × 10 3 mL/g (Song et al 2013).…”
Section: Review Of Synthetic Sorbentsmentioning
confidence: 99%